Parameter identification and estimation for stage-structured population models - Coll, Carmen; Sánchez, Elena (Zielona Góra: Uniwersytet Zielonogórski)
A stage-structured population model with unknown parameters is considered. Our purpose is to study the identifiability of the model and to develop a parameter estimation procedure. First, we analyze whether the parameter vector can or cannot uniquely be determined with the knowledge of the input-output behavior of the model. Second, we analyze how the information in the experimental data is translated into the parameters of the model. Furthermore, we propose a process to improve the recursive values of the parameters when successive observation data are considered. The structure of the state matrix leads to an analysis of the inverse of a sum of rank-one matrices.
Keywords: system identification; parameter estimation; dynamic population; discrete-time systems; rank-one matrix